PSYCHOLOGICAL PECULIARITIES OF ENGINEERING ACTIVITY - Hura, Tetiana (PSYCHOLOGICAL JOURNAL, 2017)
The article describes a research in a modern engineer’s professional activity which is quite complicated and responsible. The author highlights such psychological peculiarity of engineering activity and an engineer’s personality as specificity and clear directedness of their thinking. It is noted that a psychological peculiarity of an engineer’s professional activity is their distinctive systematic way of thinking which enables them to encompass and duly take into account a rather broad range of demands, conditions, and limitations. It is stressed that as a characteristic peculiarity of engineering activity should be regarded the essential place taken in its psychological characteristic by the controversy inherent in many people, including engineers, between certain inertance of thinking and the need in its innovative directedness stipulated by demands of technological progress. It is noted that the peculiarity of engineering activity consists in the fact that those engineers’ professional activity proves to be successful who possess an intrinsic ability of effectively overcoming inertance of thinking, developing and efficiently displaying their creative abilities and general innovative directedness when selecting, stating, and fulfilling complex engineering decisions. The author believes that in current conditions of development and application of ever more complicated machines, devices, and appliances an engineer’s professional activity takes place within large designing or industrial collectives where each employee specializes in performing certain functions or in a common work allotment. Attention is stressed in the article on another peculiarity which consists in an interesting psychological aspect connected with collective character of engineering activity, which is why a psychological peculiarity of engineering is the necessity for engineers of possessing a highly developed sense of personal responsibility for results and possible consequences of their activity. It is noted that a peculiarity of an engineer’s professional activity which has a pronounced psychological character consists in their clear realizing the fact that considerable number of engineering decisions are of a double nature, performing both a constructive and destructive role. It is accentuated that as an outstanding psychological peculiarity of engineering activity should be considered the presence of psychological conflicts of various origins and character in it. A special attention is stressed by the author that complexity in understanding the priority of a human by engineers becomes a psychological peculiarity, noting that both an engineer’s activity itself and their personality proper are to enhance their humanity and spirituality, and that responsibility should be the dominant of this activity. It is proved in the article that knowledge of psychological peculiarities enhances efficient training of engineer-leaders, development and fulfillment of their leadership potential and creativity aptitudes.